2001
DOI: 10.1111/j.1349-7006.2001.tb01116.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Induces Apoptosis via Caspase‐3 Activation in Bladder Tumor Cells

Abstract: Recently, because of its low toxicity and biological effects, chitosan has been widely used in the medical and pharmaceutical fields, e.g., for nasal or oral delivery of peptide or polar drug delivery. Here, we report a growth-inhibitory effect of chitosan on tumor cells. The growth inhibition was examined by WST-1 colorimetric assay and cell counting. We also observed DNA fragmentation, which is characteristic of apoptosis, and elevated caspase-3-like activity in chitosan-treated cancer cells. The findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(90 citation statements)
references
References 32 publications
(39 reference statements)
5
83
2
Order By: Relevance
“…Also, in this study insulin-free nanospheres had a slight hypoglycemic effect probably because many viscous soluble polysaccharides have been correlated with hypocholesterolemic and hypoglycaemic effects (Burting 2003) and this may be the case of alginate (Ohta et al 1997). Chitosan also has been used as a hypocholesterolemic and hypoglycaemic agent (Hasegawa et al 2001) and may be responsible for hypoglycemic effect observed in diabetic rats. Finally, hydrated nanospheres showed a much stronger hypoglycemic effect than did dehydrated nanospheres, likely due to differences in insulin absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in this study insulin-free nanospheres had a slight hypoglycemic effect probably because many viscous soluble polysaccharides have been correlated with hypocholesterolemic and hypoglycaemic effects (Burting 2003) and this may be the case of alginate (Ohta et al 1997). Chitosan also has been used as a hypocholesterolemic and hypoglycaemic agent (Hasegawa et al 2001) and may be responsible for hypoglycemic effect observed in diabetic rats. Finally, hydrated nanospheres showed a much stronger hypoglycemic effect than did dehydrated nanospheres, likely due to differences in insulin absorption.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, its lipoic acid component, has been shown to inhibit cell proliferation and growth, as well as induce the selective apoptosis of a number of cancer cell lines (through the downregulation of the BCL-2 protein), including lung cancer cells (Choi et al, 2009;Dozio et al, 2010;Michikoshi et al, 2013;Moungjaroen et al, 2006;Na et al, 2009;Wenzel et al, 2005). Furthermore, previous studies have also shown that chitosan inhibits cell proliferation and metastases, as well as induces apoptosis (Hasegawa et al, 2001;Kim et al, 2013). The cationic nature of LACPEG could also enhance the cellular uptake of the carrier (Peetla et al, 2014), which could, in turn, increase these effects.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Briefly, the anticancer properties of chitosan have been explained by an antiproliferative action in human gastric carcinoma cell line MGC803 cell [19], as well as in some human breast cancer cell lines [20] or in a human monocytic leukemia cell line, THP-1 [21]; by a necrotic action in various tumor cell lines [19,[22][23]; or by an apoptotic effect in several other cancer cell lines [24][25]. More specifically, Takimoto et al showed that chitosan induced apoptosis by modulating death receptor expression and activating caspase-8 on human bladder tumor cells [25] while Hasegawa et al demonstrated that chitosan induced apoptotic death of bladder tumor cells via caspase-3 activation [24]. On the other hand, Qi et al demonstrated that an antitumor mechanism induced by chitosan in human hepatocellular carcinoma was mediated by the neutralization of cell surface charge, decrease of mitochondrial membrane potential and induction of membrane lipid peroxidation [26].…”
Section: Introductionmentioning
confidence: 99%